2017
DOI: 10.2967/jnumed.116.187625
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Small-Animal PET Outcome Measures to Detect Disease Modification Induced by BACE Inhibition in a Transgenic Mouse Model of Alzheimer Disease

Abstract: In this study, we investigated the effects of chronic administration of an inhibitor of the b-site amyloid precursor protein-cleaving enzyme 1 (BACE1) on Alzheimer-related pathology by multitracer PET imaging in transgenic APPPS1-21 (TG) mice. Methods: Wild-type (WT) and TG mice received vehicle or BACE inhibitor (60 mg/kg) starting at 7 wk of age. Outcome measures of brain metabolism, neuroinflammation, and amyloid-b pathology were obtained through small-animal PET imaging with 18 F-FDG, 18 F-peripheral benzo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 39 publications
(60 reference statements)
4
24
0
Order By: Relevance
“…For brain compound and Aβ40 analysis, see Neumann et al (2015) in the AD brain. In agreement with this, a recent microamyloid-PET study performed in mice with the structurally different BACE-1 inhibitor JNJ-49146981 and using one of the "classical" Aβ PET ligands ( 18 F florbetapir) did not detect any differences between the control and treatment groups (Deleye et al, 2017). However, a longitudinal in vivo two photon microscopy study using methoxy-X04 to label Aβ in APPPS1-tg mice, with 3-month NB-360 treatment during the phase of rapid Aβ deposition, gave a more detailed picture .…”
Section: Effects Of Nb-360 Treatment On Aβ Pathologysupporting
confidence: 75%
“…For brain compound and Aβ40 analysis, see Neumann et al (2015) in the AD brain. In agreement with this, a recent microamyloid-PET study performed in mice with the structurally different BACE-1 inhibitor JNJ-49146981 and using one of the "classical" Aβ PET ligands ( 18 F florbetapir) did not detect any differences between the control and treatment groups (Deleye et al, 2017). However, a longitudinal in vivo two photon microscopy study using methoxy-X04 to label Aβ in APPPS1-tg mice, with 3-month NB-360 treatment during the phase of rapid Aβ deposition, gave a more detailed picture .…”
Section: Effects Of Nb-360 Treatment On Aβ Pathologysupporting
confidence: 75%
“…Similarly, Deleye et al . () observed significant reductions in [ 18 F]AV‐45 following chronic BACE1 inhibitor treatment, however in contrast to Maeda et al., no alterations in TSPO‐PET were observed. More recently, James et al .…”
Section: Imaging Biomarkers Of Neuroinflammationmentioning
confidence: 63%
“…Intra-hippocampal treatment with anti-Ab antibody showed decreases in [ 11 C] PiB but increases in [ 18 F]FEDAA1106 uptake in the TG mice, indicating that the treatment successfully reduced amyloid burden but was associated with increased neuroinflammation. Similarly, Deleye et al (2017) observed significant reductions in [ 18 F]AV-45 following chronic BACE1 inhibitor treatment, however in contrast to Maeda et al, no alterations in TSPO-PET were observed. More recently, James et al (2017) demonstrated that [ 18 F]GE-180 permitted detection of decreased cortical and hippocampal neuroinflammation in the APP L/S mouse following treatment with LM11A-31, a clinical AD treatment which attenuates tau phosphorylation, neurite degeneration and microglial activation.…”
Section: Pre-clinical Pet Imagingmentioning
confidence: 68%
“…We sought to confirm the efficacy of anti‐PD1 treatment in a range of different amyloid‐developing transgenic models used extensively for pharmacological testing in our respective groups (Asberom et al, ; Blanchard et al, ; Deleye et al, ; Games et al, ; Hansen et al, ; Janus et al, ). These strains develop amyloid pathology at different rates and can produce amyloid deposits of significant, compact nature (high thioflavine S reactivity: ThyAPP/PS1 M146L, and ThyAPP/PS1 A246E ) or mostly diffuse deposits (PD‐APP) (Table ).…”
Section: Resultsmentioning
confidence: 99%